Adsorption of Water Molecule in Graphene/MoS2 Heterostructure with Vacancy Defects in Mo Sites - Hari Krishna Neupane; Narayan Prasad Adhikari (Advances in Condensed Matter Physics)
First-principle calculations based on the spin-polarized density functional theory (DFT) with vdW corrections by DFT-D2 approach have been carried out to study structural, electronic, and magnetic properties of water-adsorbed graphene/MoS2 heterostructures (system-I), and water-adsorbed graphene/MoS2 heterostructures with vacancy defects in Mo sites (systems-II). We consider vacancy defects in different Mo sites such as centre-1Mo atom vacancy defect (system-IIa), left-1Mo atom vacancy defect (system-IIb), and 2Mo atom vacancy defects (system-IIc). All the systems considered in this study are structurally stable; however, the stability of defected systems decreases with an increase in defect concentrations. The calculated binding energies of HS used in this study agree with the reported work. Electronic properties of system-I and systems-II reveal that they have metallic characteristics. Our investigation shows that system-I is nonmagnetic and systems-II are magnetic. The magnetic moment in the defected systems (system-IIa, system-IIb, and system-IIc) is developed by unpaired up and down-spins of electrons created in the orbitals of atoms due to vacancy defects in Mo atoms.